Impact of the pandemic on the activities of family farmers at the municipal fair in Cascavel – Paraná, Brazil - Zanini, Elaine de Oliveira (2021)
Family farming is the main responsible for the country's food supply and is directly linked to food security and the development of the place where it operates. Thus, this work aimed to understand and analyze the difficulties of family farmers participating in the fair. Cascavel – PR to sell their products in the COVID-19 pandemic. Regarding the methodology, this research is characterized as bibliographical, exploratory and qualitative. Data collection occurred through the application of questionnaires with family farmers at the municipal fair. The survey results identified that new channels of dissemination as a strategy to increase the visibility of family farmers and product sales are very important, as in the pandemic, farmers at the Cascavel municipal fair had their sales reduced by up to 70%, due to the municipal decrees, preventing the opening of the fair, reducing the number of buses circulating, which limits access to the fair, especially for the elderly who use this means of transport and because of the closing of schools, affecting participants in programs such as the PAA (School Feeding Program) and PNAE (National School Feeding Program). It is concluded that the COVID-19 pandemic will have repercussions in various ways on family farming, in relation to family farmers at the municipal fair, the research revealed that local strategies are needed to mitigate its negative effects.